Nuclear waste management facilities : advances, environmental impacts, and future prospects - Rahman, Rehab O. Abdel (Academic Press, 2024)
Nuclear Waste Management Facilities: Advances, Environmental Impacts, and Future Prospects examines best practices and recent trends in improving nuclear safety and reducing the negative environmental impacts of nuclear waste.